Vibration isolation at the level of footing using modified concrete. (2020) - Therese, Nimmy; Sruthy, S.; Mini, K.M.
Abstract: Isolation of vibrations from the building during a seismic event is a proven practice to reduce damage to buildings. This paper studies the effectiveness of a new technique of vibration isolation. A modified concrete layer with damping characteristics is provided around the footing to isolate the building from the vibrations during an earthquake. The modified concrete is prepared by using varying percentages of crumb rubber and steel slag as a replacement to fine aggregates. Apart from providing the modified concrete as a confining layer, modification is done to the structural material in footing itself and is investigated for its effectiveness in improving the seismic performance. A multi-storeyed building is selected, modeled in ANSYS Workbench, modified concrete is incorporated in two different ways in and around footing and the seismic responses are compared with that of a conventional building without any modifications. Accelerogram from El – Centro Earthquake is used as the input loading. The material properties required for the analysis is obtained by conducting experiments. The energy dissipation capacity of the modified concrete with various percentages of fibres is studied using the hysteresis loops generated in ANSYS. Both the techniques showed a improvement in the seismic performance, providing the modified concrete as a structural material exhibited better results. Sleel slag modified concrete has better energy dissipation capacity than crumb rubber.